2013
DOI: 10.1145/2461912.2461998
|View full text |Cite
|
Sign up to set email alerts
|

RealBrush

Abstract: Figure 1: A simple painting created by our system. Left to right: (a) shows oil (left) and plasticine (right) exemplars which are used to synthesize the painting in (b). The foreground flower strokes use oil exemplars, while the background strokes use plasticine and are smoothed with our smudging tool using. (c) (d) show close-ups of the smearing and smudging effects. AbstractConventional digital painting systems rely on procedural rules and physical simulation to render paint strokes. We present an interactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Stroke visibility may be "haloed" for greater clarity (Elber, 1995b). More sophisticated texture-based stroke models include "RealBrush", which uses multiple scanned paint strokes to model paint mixing (Lu et al, 2013) and "DecoBrush" (Lu et al, 2014), which uses procedurally-defined line art textures. These stroke textures may also be drawn directly in a WYSIWYG interface (Kalnins et al, 2002;Saito, 2015, 2016).…”
Section: Stroke Renderingmentioning
confidence: 99%
“…Stroke visibility may be "haloed" for greater clarity (Elber, 1995b). More sophisticated texture-based stroke models include "RealBrush", which uses multiple scanned paint strokes to model paint mixing (Lu et al, 2013) and "DecoBrush" (Lu et al, 2014), which uses procedurally-defined line art textures. These stroke textures may also be drawn directly in a WYSIWYG interface (Kalnins et al, 2002;Saito, 2015, 2016).…”
Section: Stroke Renderingmentioning
confidence: 99%
“…By design-based implementation research, teachers designed a student-centered unit aligned to the Next Generation Science Standards (NGSS) in which classroom technology is applied together with researchers and course specialists. Lu [8] applied 3D digital technique in painting teaching, and put forward an interactive and data-driven painting system which applies scanned images of real natural media to synthesize both new strokes and complex stroke interactions, which obviates the need for physical simulation. Teaching practice showed that, 3D digital technique is more beneficial to improve art effect of painting.…”
Section: State Of the Artmentioning
confidence: 99%
“…Related to fabrication of paintings, non-photorealistic rendering aims to generate stylized compositions that reflect artistic intent [Bot09, BNTS07, HE04, WWF * 14, LC14, CAS * 97, SLKD16]. Projects about simulation of different painting media, including watercolor, create a virtual painting or investigate the properties of the media [CKIW15,LBDF13]. We aim to fabricate an artistic version similar to the non-photorealistic rendering based on the input photograph.…”
Section: Related Workmentioning
confidence: 99%